Optimization and evaluation of reduced graphene oxide hydrogel composite as a demulsifier for heavy crude oil-in-water emulsion - Fong, K.K.; Tan, Inn Shi; Foo, H.C.Y.; Lam, M.K.; Tiong, Adrian Chiong Yuh; Lim, S. (CHEMICAL INDUSTRY PRESS CO LTD, 2021)
The rising production of produced water from oilfields had been proven to bring detrimental environmental effects. In this study, an efficient, recyclable, and environmental-friendly reduced graphene oxide immobilized κ-Carrageenan hydrogel composite (κCaGO) was fabricated as an alternative sorbent for crude oil-in-water demulsification. Polyethyleneimine (PEI) was employed to form a stable hydrogel composite. The conditions for the immobilization of graphene oxide (GO) on PEI-modified κ-Carrageenan (κC) beads were optimized appropriately. An immobilization yield of 77% was attained at 2% PEI, 2 h immobilization activation time, and pH 6.5. Moreover, the synthesized κCaGO is capable of demulsification with an average demulsification efficiency of 70%. It was found that the demulsification efficiency increases with salinity and κCaGO dosage, and it deteriorates under alkaline condition. These phenomena can be attributed to the interfacial interactions between κCaGO and the emulsion. Furthermore, the κCaGO can be recycled to use for up to six cycles without significant leaching and degradation. As such, the synthesized κCaGO could be further developed as a potential sorbent substitute for the separation of crude oil from produced water.